High pressure dissipative granular materials for earthquake protection of houses - Bek, Marko (Anali PAZU, 2013)
In the recent years different types of dampers for structural control in civil engineering have been developed, where one of the most promising solutions are viscoelastic dampers. In this paper we demonstrate that by utilizing knowledge on the effect of inherent hydrostatic pressure on the time- and frequency-dependent behavior of polymers it is possible to design and build the ultimate insulation systems for civil engineering applications. An optimal solution is achieved by using highly pressurized multimodal granular polymeric materials. The results on case material, Thermoplastic Polyurethane, showed that by increasing inherent pressure of the material from 1 bar to 2000 bar the frequency at which material exhibits its maximal damping properties was shifted from 37 kHz, at P=1 bar to 235 Hz at P=2000 bar. At the same time, the increase of inherent hydrostatic pressure from 1 bar to 2000 bar changes material stiffness up to 2.5 times, while the damping properties increase up to 5.2 times.
Keywords: disipativni granulirani materiali; dissipative granular materials; earthquake protection; pressure; protipotresna gradnja; protipotresna zaščita; termoplastični poliuretan; thermoplastic polyurethane; tlak; viscoelasticity; viskoelastičnost